ARCHITECTURAL CHARACTERISTICS STUDY ON COMMUNITY MOSQUES IN PRIANGAN 1900 – 1942 - Istiqomah, Esti; Budi, Bambang Setia (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2013)
AbstractPriangan was a region with a distinctive historical background and administrative unity. The region consisted of 7 regencies in present West Java Province. There were some old community mosques in the region. The aim of this paper is to formulate architectural characteristics of Priangan old community mosques and their overall development. The mosques are no longer observable today. Therefore, the study is referring to old documentations. The oldest available documentations of such mosques were presented in the form of photos from Dutch colonial era, after the ethical policy. Therefore, the study is limited from the year 1900 to 1942. Based on the photos, the mosques were resketched by outlining the intended variables, which are building mass, transitional space, and roof. There were some common architectural characteristics that can be concluded from Priangan old community mosques. The common characters are single mass, surrounding verandah, and two stacked pyramidal roof. On the overall development, the mosques showed the peak of architectural characteristics variations on the photos that were taken in the year 1925.Keywords: mosque, Priangan, colonial, characteristic, architecture AbstrakPriangan merupakan suatu wilayah yang memiliki kesamaan latar historis dan pernah memiliki kesatuan administrasi. Wilayah ini meliputi 7 kabupaten di Provinsi Jawa Barat saat ini. Di wilayah tersebut terdapat masjid-masjid komunitas lama. Makalah ini bertujuan untuk merumuskan karakteristik arsitektural masjid- masjid komunitas lama yang ada di Priangan serta kecenderungan perkembangan keseluruhannya. Masjid- masjid tersebut saat ini sudah tidak dapat diamati lagi di lapangan. Oleh karena itu, studi karakteristik dilakukan melalui sumber dokumentasi bersejarah. Dokumentasi masjid-masjid tersebut mulai muncul pada masa kolonial Belanda setelah politik etis dalam bentuk foto. Oleh karena itu, kurun waktu kajian dibatasi antara tahun 1900 hingga tahun 1942. Dari foto-foto tersebut, masjid kemudian di sketsa ulang untuk memperjelas variabel-variabel yang akan dianalisis, yaitu massa, ruang, dan atap. Dari hasil analisis, didapatkan karakteristik arsitektural masjid komunitas lama di Priangan yang umum, yaitu memiliki massa tunggal, selasar keliling, dan atap tumpang 2 tumpuk. Kemudian dalam foto masjid-masjid yang diambil tahun1925, karakter arsitektural masjid menjadi semakin beragam. Kata kunci: masjid, Priangan, kolonial, karakteristik, arsitektur